PERSONAL HYGIENE DENGAN KEJADIAN PENYAKIT SKABIES PADA SANTRI WUSTHO (SMP) DI PESANTREN AL-FALAH BANJARBARU - Rahmi, Norhalida; Arifin, Syamsul; Pertiwiwati, Endang (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2016)
Scabies is a contagious infectious disease caused by infection and sensitization by Sarcoptesscabei var hominis mites (Sarcoptes sp.). transmission can occur directly and indirectly. one ofthe effects of scabies is poor personal hygiene. To determine the correlation personal hygienewith incidence of scabies in Islamic boarding Wustho students (SMP) Al Falah PuteraBanjarbaru. This study was a correlational study with cross-sectional approach, using samplingtechniques probality sampling with simple random sampling. The population was all studentswere Islamic boarding wustho in first class as many as 341 students. Total respondent were 184students in Islamic boarding. Analysis of the Personal hygiene exposed to scabies 24% good,good personal hygiene was not affected by scabies 76%. Personal hygiene badly affected byscabies 53%, poor personal hygiene was not affected by scabies 47%. Result of correlation chisquare test p value = 0.000 and (r) = 12.590. personal hygiene associated with the incidence ofscabies. Personal hygiene was one of effort that can prevent the incidence of scabies.